Enhanced solar steam generation of hydrogel composite with aligned channel and shape memory behavior. (1st March 2021) - He, Jingxian; Fan, Yukang; Xiao, Chaohu; Liu, Fang; Sun, Hanxue; Zhu, Zhaoqi; Liang, Weidong; Li, An
Abstract: Solar steam generation with unique and highly efficient interface-evaporation manner by directly harvesting solar energy has emerged as one of promising strategies for production of fresh water. Herein, an acetylene black (ACET) doped dual-crosslinked hydrogel composite, which derived from sodium alginate (SA) and polyacrylamide (PAM), has been fabricated via a simple directional freezing treatment followed by a solvent-free polymerization for solar steam generation. The prepared hydrogel (named as ACET/PAM/SA-LN( 25 )) shows the long-range vertically aligned channel structures which is entirely different from the same hydrogel prepared by traditional method (ACET/PAM/SA). Due to its unique microstructures, the ACET/PAM/SA-LN( 25 ) hydrogel exhibits excellent light absorption (ca. 95%) and has more fast water transmission performance, e.g., the water content ( Q ) was up to 14.42 g per gram of the corresponding xerogel, which is higher than that of ACET/PAM/SA (8.28 g g −1 ). The solar steam generation device based on ACET/PAM/SA-LN( 25 ) hydrogel shows a very high energy conversion efficiency of up to 93% under 1 sun radiation. Interestingly, the hydrogel composite exhibits excellent processability and flexibility with shape memory property in the swelling state, which has great advantages over those traditional fragile hydrogels and thus shows significant potential for real operation in solar steam generation. Graphical abstract: Image 1 Highlights: ACET/PAM/SA-LN( 25 ) hydrogel with stable aligned channel was synthesized. Combining directional freezing and solvent-free polymerization were firstly used. Hydrogel shows enhanced robustness and flexibility with shape memory property. Hydrogel exhibits outstanding energy conversion efficiency. Hydrogel is environment-friendly with green synthetic strategy and reusable property.